Hello, world: an internationalization at home project for computing for social good - Aheer, Komal (My University, 2019)
We have developed and piloted a cross-institution activity as part of an Internationalization at Home (IaH) initiative to expose first year computer science students to the concept of computing for social good in an international context. We explore how differences in culture can influence students’ perceptions and approaches to computing for social good.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: information technology; social good